2016
DOI: 10.1088/1742-6596/712/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of correlations in the atom motion upon hydrogen intercalation into ReO3lattice

Abstract: Abstract. The influence of hydrogen intercalation on the local structure of rhenium trioxide is studied in-situ by the Re L3-edge EXAFS spectroscopy and analysed using a novel approach, based on the use of evolutionary algorithm and wavelet transform. The proposed method allows us to perform accurate EXAFS analysis within the multiple-scattering approach taking into account contributions from outer coordination shells and to access the information on correlations in atomic thermal motion. IntroductionThe analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…These findings are in agree-ment with expected anisotropy of copper motion, as observed for Cu 3 N in diffraction studies [20,21]: the vibrations of copper atoms in the direction orthogonal to -N-Cu-N-chains are significantly larger than their vibrations along the chains, and they also grow faster upon increasing temperature. Note that similar trends have been observed by us previously in perovskite-type ReO 3 [48,49,14] and ScF 3 [38].…”
Section: Msrd Factors and Effective Force Constantssupporting
confidence: 90%
See 4 more Smart Citations
“…These findings are in agree-ment with expected anisotropy of copper motion, as observed for Cu 3 N in diffraction studies [20,21]: the vibrations of copper atoms in the direction orthogonal to -N-Cu-N-chains are significantly larger than their vibrations along the chains, and they also grow faster upon increasing temperature. Note that similar trends have been observed by us previously in perovskite-type ReO 3 [48,49,14] and ScF 3 [38].…”
Section: Msrd Factors and Effective Force Constantssupporting
confidence: 90%
“…Pronounced anisotropy of Cu atoms vibrations was detected in Cu 3 N, as it is known for O atoms in ReO 3 . Moreover, we have found that strong correlations in the motion of atoms along -N-Cu-N-atomic chains are present in Cu 3 N, as was found in -Re-O-Re-atomic chains in ReO 3 [49]. Interatomic interactions in Cu 3 N have also strong directional dependence, as expected for materials with pronounced covalent bonding.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations